2023
DOI: 10.3389/fcimb.2023.1255905
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis of human peripheral blood mononuclear cells stimulated by Mycobacterium tuberculosis antigen

Jing Wei,
Fangzheng Guo,
Yamin Song
et al.

Abstract: BackgroundMycobacterium tuberculosis antigen (Mtb-Ag) is a polypeptide component with a molecular weight of 10-14 kDa that is obtained from the supernatant of the H37Ra strain after heat treatment. It stimulates the activation and proliferation of γδT cells in the blood to produce an immune response against tuberculosis. Mtb-Ag is therefore crucial for classifying and detecting the central genes and key pathways involved in TB initiation and progression.MethodsIn this study, we performed high-throughput RNA se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…In the study conducted by Jing Wei et al, the Kyoto Genomic Encyclopedia and single gene enrichment analysis of peripheral blood mononuclear cells from the Asian population of Mtb-Ag stimulated and control samples revealed a significant enrichment of the TNF signaling pathway, which is closely associated with tuberculosis. Furthermore, it was observed that this pathway coexpressed with five pathways in the protein-protein interaction network, all of which exhibited upregulation under Mtb-Ag stimulation (24). Yukari C Manabe et al conducted a randomized clinical trial in which 850 HIV patients from 10 African countries were evaluated for 26 plasma biomarkers using a combination of multiple immunoassays and enzyme-linked immunosorbent assays.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Jing Wei et al, the Kyoto Genomic Encyclopedia and single gene enrichment analysis of peripheral blood mononuclear cells from the Asian population of Mtb-Ag stimulated and control samples revealed a significant enrichment of the TNF signaling pathway, which is closely associated with tuberculosis. Furthermore, it was observed that this pathway coexpressed with five pathways in the protein-protein interaction network, all of which exhibited upregulation under Mtb-Ag stimulation (24). Yukari C Manabe et al conducted a randomized clinical trial in which 850 HIV patients from 10 African countries were evaluated for 26 plasma biomarkers using a combination of multiple immunoassays and enzyme-linked immunosorbent assays.…”
Section: Discussionmentioning
confidence: 99%